The Ottoman Ibadis of Cairo: A History - Love Jr, Paul M. (Cambridge University Press, 2023)
Paul M. Love, Jr. explores the history of the minority Ibadi Muslim community in Cairo from the seventeenth to the early twentieth centuries. Using a unique range of sources, Love both illuminates the events of Egyptian history and highlights the role of the Ibadis in shaping political, religious, and commercial life in Ottoman-era Cairo.
Keywords: Emigration -- Djebel Nefousa -- Egypte; Emigration -- Djerba -- Egypte; Emigration -- Mzab -- Le Caire

الحضور النفوسي في مصر من خلال مخطوطات وكالة الجاموس - حاج امحمد, عيسى (علماء وأعلام ومعالم نفوسة وزوارة ماضيا وحاضرا, 2024)
Keywords: Emigration -- Djebel Nefousa -- Egypte

الوقف الثقافي الإباضي والمالكي في مصر دراسة مقارنة - مصلح, أحمد بن مهني (اباديكا, 2024)
Keywords: Bibliothèques -- Le Caire; Emigration -- Djebel Nefousa -- Egypte; Emigration -- Djerba -- Egypte; Emigration -- Mzab -- Le Caire; Manuscrits -- Le Caire

رحلة بعض علماء الجبل وزوارة للمدن والبلدان المجاورة خلال العصر العباس وحتى انتقال الدولة الفاطمية إلى مصر (361-140هـ/758-971م) - حدود, منى علی (نفوسة وزوارة : الاعلام والعلماء والمعالهم, 2022)
Keywords: Emigration -- Djebel Nefousa -- Egypte; Vie intellectuelle -- Djebel Nefousa